Labour market dynamics from a regional perspective: the multi-account system - Anette Haas; Thomas Rothe (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
In the last years the analysis of flow figures turned out to highly informative for labour market research and policy advice. Among researchers it is a well known fact that cross-sectional information about labour market is not sufficient to understand ungoing development. A pure sequence of employment and unemployment figures would hide the turnover in the market. Here we follow the useful analytical framework of transitional labour markets dealing centrally with flow figures. By developing the multiaccount system (MAS) we go some steps ahead compared to indicators like job and labour turnover rates. First we combine the information of administrative data of the micro level with macro data containing pupils, self employed, retired persons. Embedded in an external framework, which is given by demography (birth, death, moving in and out), the MAS describes the transition process of the labour market on the regional level and contains all 180 local employment agencies in Germany. The multiaccount system thus serves as a basis for strategically aligning each agency with the individual local situation of the labour market by explicitly taking into account the regional specifics. Thus it helps for future strategic decisions of active labour market policy. The creation of models for supporting regional monitoring and benchmarking is already far advanced and initial basic versions are tested in practice. For estimating the unknown transitions of the data matrix we use a new algorithm the so called ADETON tool, which has the additional merit comparing to other entropy maximizing methods, that constraints can be formulated in a fuzzy way rather than exactly. Further we demonstrate on the basis of the agency Heilbronn some practice and numerical examples. Thus we present transitions into and out of unemployment and also from vocational training to employment. We believe that the analytical potential of this instrument is not yet exhausted. In any event, it is already clear that the information content of this model by far exceeds that of a system of individual indicators. Details and relations of the regional labour market become apparent which show a high-resolution image of possible obsolete structures or increasing labour market dynamics. The model thus gives clear hints as to the scope and limits of the active labour market policy.
Keywords: R15; R23; J23; J63; J68; 330; Arbeitskräftemobilität; labour turnover; job turnover; Berufsverlauf; Arbeitslosigkeit; Erwerbstätigkeit; arbeitsmarktpolitische Maßnahme; regionale Disparität